Deep Learning vs. Traditional Machine Learning in Financial Market Predictions - Wasiu Eyinade; Onyinye Jacqueline Ezeilo; Ibidapo Abiodun Ogundeji (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Financial market predictions have long relied on machine learning techniques to analyze historical data, identify patterns, and forecast future trends. Traditional machine learning models such as linear regression, decision trees, and support vector machines (SVM) have been widely used for predictive modeling in stock price forecasting, risk assessment, and algorithmic trading. However, the rise of deep learning has introduced more sophisticated methods capable of capturing complex, non-linear relationships in financial data. Deep learning models, particularly recurrent neural networks (RNNs), long short-term memory (LSTM) networks, and convolutional neural networks (CNNs), have demonstrated superior performance in extracting temporal dependencies and handling large, high-dimensional datasets. Despite their advantages, deep learning models come with challenges such as high computational costs, longer training times, and the need for extensive labeled datasets. In contrast, traditional machine learning models are more interpretable, require less computational power, and are often preferred when working with structured financial data. Feature engineering plays a crucial role in traditional models, while deep learning models automatically extract features from raw data, reducing the need for manual intervention. The trade-off between interpretability and predictive accuracy remains a key consideration for financial analysts and institutions when selecting between these approaches. Recent advancements in hybrid models combining traditional machine learning techniques with deep learning architectures have shown promising results in improving financial market predictions. These models leverage the strengths of both methodologies by integrating feature engineering from traditional approaches with the automated learning capabilities of deep neural networks. Additionally, the adoption of reinforcement learning and generative adversarial networks (GANs) has further enhanced predictive modeling in trading strategies and risk management. As financial markets become increasingly complex, the future of predictive analytics will likely involve a combination of deep learning and traditional machine learning techniques. While deep learning offers improved accuracy and adaptability, traditional models remain relevant due to their interpretability and efficiency. Striking a balance between these approaches will be critical in developing robust financial forecasting systems.